Development of a Chemical Methodology for the Preparation of Peptide Thioesters Applicable to Naturally Occurring Peptides Using a Sequential Quadruple Acyl Transfer System. Issue 4 (28th April 2015) - Tsuda, Yusuke; Shigenaga, Akira; Tsuji, Kohei; Denda, Masaya; Sato, Kohei; Kitakaze, Keisuke; Nakamura, Takahiro; Inokuma, Tsubasa; Itoh, Kohji; Otaka, Akira
Abstract Peptide thioesters are very useful in protein chemistry, and chemistry‐ and biochemistry‐based protocols are used for the preparation of thioesters. Among such protocols, only a few biochemistry‐based approaches have been use for naturally occurring peptide sequences. The development of chemistry‐based protocols applicable to natural sequences remains a challenge, and the development of such methods would be a major contribution to protein science. Here, we describe the preparation of peptide thioesters using innovative methodology that features nickel(II)‐mediated alcoholysis of a naturally occurring peptide sequence, followed by O−N and N−S acyl transfers. This protocol involves sequential quadruple acyl transfer, termed SQAT. Notably, the SQAT system consists of sequential chemical reactions that allow naturally occurring peptide sequences to be converted to thioesters without requiring an artificial chemical unit.